Knowledge, attitude/perception, and practice related to seasonal influenza vaccination among caregivers of young Thai children: A cross-sectional study. - Chareeya Thanee (Public Library of Science (PLoS), 2021)
Background Seasonal influenza vaccination uptake among young children in Thailand is low despite national recommendation for vaccination. We implemented a knowledge, attitude/perception, and practice survey to understand determinants of influenza vaccination in children aged six months to two years. Methods Using a cross-sectional design, we interviewed caregivers of 700 children in seven hospitals using a structured questionnaire to collect information on caregivers' and children's demographic characteristics, and caregivers' knowledge of influenza illness and national vaccine recommendation, attitude/perception toward influenza vaccine, and information sources. We verified children's influenza vaccination status against medical records (vaccinated vs. unvaccinated). Logistic regression was used to examine factors independently associated with children receiving influenza vaccination in the 2018 season using the dataset restricted to only children's parents. Variables associated with vaccination at p-value ≤0.20 were included in subsequent multivariable logistic models. Significant independent determinants of children's influenza vaccination and collinearity of covariates were assessed. The final model was constructed using a stepwise backward elimination approach with variables significant at p-value <0.05 retained in the model. Results During August 2018-February 2019, 700 children's caregivers completed the questionnaire; 61 (9%) were caregivers of vaccinated children. Caregivers of the vaccinated children were statistically more likely to have higher education (61% vs. 38%; p-value<0.01) and to know of influenza illness (93% vs. 76%; p-value = 0.03) than those of the unvaccinated group. Factors associated with children receiving influenza vaccination were identifying healthcare providers as a primary source of information about influenza illness for parents (adjusted odds ratio [aOR], 2.8; 95% confidence interval [CI], 1.3-6.0), parents' strongly agreeing with the national recommendation for influenza vaccination in young children (aOR, 2.9; 95% CI, 1.5-5.9), using health insurance provided by the government or parent's employer for children's doctor visits (aOR, 2.6; 95% CI, 1.1-6.6), and the children's history of receiving influenza vaccination in the 2017 season or earlier (aOR, 3.2; 95% CI, 1.4-7.8). Conclusion The majority of caregivers of children in this study had knowledge of influenza illness and influenza vaccine. Caregivers reported various sources of information regarding influenza illness and the vaccine, but healthcare providers remained the most trusted source. Children's history of influenza vaccination in prior season(s) was the strongest determinant of children being vaccinated for influenza in the current season.